Nucleic Acid-Sensing Pathways During SARS-CoV-2 Infection: Expectations versus Reality - Mdkhana B; Saheb-Sharif Askari N; Ramakrishnan RK; Goel S; Hamid Q; Halwani R (Dove Medical Press, 2021)
Bushra Mdkhana,1 Narjes Saheb Sharif-Askari,1 Rakhee K Ramakrishnan,1 Swati Goel,1 Qutayba Hamid,1– 3 Rabih Halwani1,2 1Sharjah Institute of Medical Research, College of Medicine, University of Sharjah, Sharjah, United Arab Emirates; 2Department of Clinical Sciences, College of Medicine, University of Sharjah, Sharjah, United Arab Emirates; 3Meakins-Christie Laboratories, Research Institute of the McGill University Health Center, Montreal, Quebec, CanadaCorrespondence: Rabih HalwaniCollege of Medicine, University of Sharjah, Sharjah, United Arab EmiratesEmail rhalwani@sharjah.ac.aeAbstract: The coronavirus disease 2019 (COVID-19) pandemic has affected millions of people and crippled economies worldwide. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) responsible for this pandemic has triggered avid research on its pathobiology to better understand the pathophysiology of COVID-19. In the absence of approved antiviral therapeutic strategies or vaccine platforms capable of effectively targeting this global threat, the hunt for effective therapeutics has led to many candidates being actively evaluated for their efficacy in controlling or preventing COVID-19. In this review, we gathered current evidence on the innate nucleic acid-sensing pathways expected to be elicited by SARS-CoV-2 and the immune evasion mechanisms they have developed to promote viral replication and infection. Within the nucleic acid-sensing pathways, SARS-CoV-2 infection and evasion mechanisms trigger the activation of NOD-signaling and NLRP3 pathways leading to the production of inflammatory cytokines, IL-1β and IL-6, while muting or blocking cGAS-STING and interferon type I and III pathways, resulting in decreased production of antiviral interferons and delayed innate response. Therefore, blocking the inflammatory arm and boosting the interferon production arm of nucleic acid-sensing pathways could facilitate early control of viral replication and dissemination, prevent disease progression, and cytokine storm development. We also discuss the rationale behind therapeutic modalities targeting these sensing pathways and their implications in the treatment of COVID-19.Keywords: COVID-19, SARS-CoV-2, innate immune system, nucleic acid sensing, immune evasion, NLRP3, cGAS-STING, coronavirus